2022
DOI: 10.1371/journal.pone.0265525
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of pitching velocity with anthropometric measurements for adult male baseball pitchers in tryout settings

Abstract: Several studies have investigated factors influencing baseball pitching velocity. However, some measurements require expensive equipment, and some tests need familiarity to perform well. In this study, we adopted field tests executed using affordable equipment in a tryout event for a professional baseball team in Taiwan, 2019. We use half day to test 64 players, and the result of measurement are used to develop a model for predicting pitching velocity of amateur adult pitchers (age: 23.9 ± 2.8 years; height: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Validation studies have previously shown that this system is useful for evaluating ball velocity, pitching motion, spin axis, and spin rate [15][16][17]. The Rapsodo Pitching unit was set up according to the manufacturer's instructions and was not moved or changed during the measurement of each participant.…”
Section: Ball-related Metricsmentioning
confidence: 99%
“…Validation studies have previously shown that this system is useful for evaluating ball velocity, pitching motion, spin axis, and spin rate [15][16][17]. The Rapsodo Pitching unit was set up according to the manufacturer's instructions and was not moved or changed during the measurement of each participant.…”
Section: Ball-related Metricsmentioning
confidence: 99%
“…In a study that analyzed the effects of body composition of elite players playing different positions on baseball performance, pitchers showed higher height, weight, and muscle mass than players in other positions, which were positively correlated with ball velocity (Carvajal et al, 2009). Additionally, in another study on the relationship between physical performance and pitching velocity of pitchers in a professional baseball team tryout, pitchers with higher muscle strength and power had a faster pitching velocity (Huang et al, 2022). Based on these findings, the physical characteristics of pitchers were significantly correlated with ball velocity, suggesting the importance of muscle strength and power improvement training of the trunk and extremities to increase ball velocity (Stodden et al, 2005;Wong et al, 2022;Yamada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%